Edukasi Kesadaran Hak dan Kewajiban Anak Sebagai Warga Negara di MA Mizanul 'Ulum Sanrobone - Rezah, Farah Syah; Sapada, Andi Tenri; Hamzah, Yuli Adha (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
Rights and obligations are inherent in human beings and Indonesian citizens. In the school environment, rights and obligations are increasingly inherent for students as citizens. The UMI PKM team had the opportunity to visit one of their partners located in Sanrobone Village, Takalar Regency, namely MA Mizanul Ulum. Before the Community Service activity was carried out, the PKM team found various problems occurring with the partners, such as some students still frequently skipping school, not doing their homework, being late often, and violating other rules. Therefore, the PKM Team conducted legal counselling activities with the aim of helping students understand the importance of raising awareness of rights and obligations regarding rules and regulations as the basis for creating order and justice in the school environment. This activity is conducted thru lecture and discussion methods. The results of the activity show an increase in awareness of the rights and obligations of students at MA Mizanul Ulum. The implications of this activity are that it can cultivate legal awareness from an early age, instill discipline and a sense of responsibility, and shape students' characters to be integrated and well-rounded.